FEMALE STUDENTS’ BEHAVIOUR OF MENSTRUAL HYGIENEEN TASIKMALAYA - Rani Sugih M; Neni Nuraeni; Hani Handayani (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Menstrual hygiene is an activity to maintain genital hygiene during menstruation. Reproductive health behaviour among adolescents is one thing that must be considered, including menstrual hygiene. The purpose of this study was to determine the menstrual hygiene behaviour of female students. This study was quantitative descriptive research. The sample was chosen using the total sampling technique. 98 female students in SMK X involved in this study. The univariate analysis applied frequency distribution. The results found that most of the menstrual hygiene behaviours were in the poor category which is 56 students (57.1%) and 42 (42.9%) students were in a good category. It is expected that the school would provide facilitates, health educations, and collaboration with PHC to support female students in dealing with menstrual hygiene behaviour.Keywords: Behaviour, female students, menstrual hygiene.